2009
DOI: 10.1371/journal.ppat.1000574
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpu Neutralizes the Antiviral Factor Tetherin/BST-2 by Binding It and Directing Its Beta-TrCP2-Dependent Degradation

Abstract: Host cells impose a broad range of obstacles to the replication of retroviruses. Tetherin (also known as CD317, BST-2 or HM1.24) impedes viral release by retaining newly budded HIV-1 virions on the surface of cells. HIV-1 Vpu efficiently counteracts this restriction. Here, we show that HIV-1 Vpu induces the depletion of tetherin from cells. We demonstrate that this phenomenon correlates with the ability of Vpu to counteract the antiviral activity of both overexpressed and interferon-induced endogenous tetherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
333
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(380 citation statements)
references
References 61 publications
34
333
3
1
Order By: Relevance
“…2E). In general, our results corroborate those reported in several recent manuscripts (27,32,35), which have each found that the two cytosolic lysines have no phenotype with respect to viral egress or surface down-regulation by Vpu. However, as described above, disagreement remains regarding the contribution that these lysines make toward Vpu-dependent ubiquitination.…”
Section: Vpu-dependent Bst-2 Ubiquitinationsupporting
confidence: 92%
See 2 more Smart Citations
“…2E). In general, our results corroborate those reported in several recent manuscripts (27,32,35), which have each found that the two cytosolic lysines have no phenotype with respect to viral egress or surface down-regulation by Vpu. However, as described above, disagreement remains regarding the contribution that these lysines make toward Vpu-dependent ubiquitination.…”
Section: Vpu-dependent Bst-2 Ubiquitinationsupporting
confidence: 92%
“…Note that in both cell lines, egress of the vpu2/6 virus displays a consistent intermediate phenotype that we and others have previously observed. Although BST-2 is not degraded in the presence of Vpu2/6, several labs including our own have shown that BST-2 binds to wild type Vpu and Vpu2/6 equally well (27,40,47). Therefore, the Vpu2/6 partial egress phenotype likely results from the transient sequestration of BST-2 within an intracellular compartment.…”
Section: Ubiquitination Of Bst-2 In the Presence Of Vpu-mentioning
confidence: 68%
See 1 more Smart Citation
“…Tetherin antagonism by Vpu also depends in part on the recruitment of βTrCP-2, an adaptor protein for an E3 ubiquitin ligase involved in targeting tetherin for degradation (24,25,30,31). Hence, substitutions in a conserved DSGxxS motif in the cytoplasmic tail of Vpu (S52,56N) that prevent the recruitment of βTrCP-2 partially impair tetherin antagonism by preventing its degradation, but not its endosomal sequestration (25,(30)(31)(32)(33). These substitutions are also known to abrogate CD4 down-regulation, but do not affect Vpu-mediated down-modulation of NTB-A (23).…”
Section: Deletion Of Vpu Increases the Susceptibility Of Hiv-1-infectmentioning
confidence: 99%
“…38 Vpu interferes with tetherin by targeting tetherin for degradation, in a manner similar to that by which Vpu downregulates CD4. 39,40 Sequence variations in the TM domain of tetherin that affect sensitivity to Vpu have been identified. 41,42 Formation of Vpu/tetherin hetero-oligomers through direct interactions between their TM domains may therefore be essential for Vpu function, and these hetero-oligomers may be structurally related to Vpu homo-oligomers.…”
Section: Introductionmentioning
confidence: 99%